2021
DOI: 10.3390/s21031003
|View full text |Cite
|
Sign up to set email alerts
|

An Optical Chiral Sensor Based on Weak Measurement for the Real-Time Monitoring of Sucrose Hydrolysis

Abstract: A chiral sensor with optical rotation detection based on weak measurement for the kinetic study of sucrose hydrolysis is presented. Based on the polarization modulation to the pre-selection state, the optical rotation of chiral sample was accurately determined through the central wavelength shift of the output spectrum. With this approach, the concentration response curves of sucrose and its hydrolysis products, i.e., fructose and glucose, were experimentally obtained for the hydrolysis analysis. By collecting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The most widely used sweetener, sucrose, is not only extracted mostly from sugarcane but also from fruits and vegetables. Up to 99.5% of final prepared white sugar is sucrose, which is the most crucial component in the synthesis of sugar [ 1 , 2 ]. Animals consume sucrose to maintain their energy levels, which affects their lipid metabolism and insulin effectiveness [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most widely used sweetener, sucrose, is not only extracted mostly from sugarcane but also from fruits and vegetables. Up to 99.5% of final prepared white sugar is sucrose, which is the most crucial component in the synthesis of sugar [ 1 , 2 ]. Animals consume sucrose to maintain their energy levels, which affects their lipid metabolism and insulin effectiveness [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Li et al [ 29 ] reported a polarimetric method to measure sucrose inversion, in real-time, at concentrations range of M. Instead of sodium D light, Li et al used pulses of polarized light with a Gaussian distribution centered at 830 nm and amplitude of 10 nm, generated by a super luminescent diode (SLD) with a Gaussian filter. The reaction of sucrose with INV decreases the optical activity in the solution, changing the photon’s polarization at the optical interface and displacing the Gaussian center distribution of the photon wavelengths [ 29 ]. This is known as the photonic spin Hall effect due to the spin–orbit coupling in polarized photons.…”
Section: Analytical Chemistry Methodsmentioning
confidence: 99%
“…This is known as the photonic spin Hall effect due to the spin–orbit coupling in polarized photons. This spin–orbit coupling is a weak interaction that the authors managed to amplify under the approximation of quantum weak measurement, achieving the detection of sucrose in a linear range from 2.28 M to 50.2 mM [ 29 , 30 ].…”
Section: Analytical Chemistry Methodsmentioning
confidence: 99%
“…34 Furthermore, they also utilized quantum weak measurement to monitor the real-time hydrolysis process of sucrose in 2021. 35 The optical rotation sensor has the capability to detect amino acids and proteins. 36 Some previous studies on glucose or chiral optical sensors based on weak measurement have demonstrated encouraging outcomes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In 2016, a research group at Tsinghua University applied quantum weak measurement to detect glucose concentration . Furthermore, they also utilized quantum weak measurement to monitor the real-time hydrolysis process of sucrose in 2021 . The optical rotation sensor has the capability to detect amino acids and proteins .…”
Section: Introductionmentioning
confidence: 99%